Sealing material for vehicle window glass
By integrating a flocked layer with conductive fibers into the sealing member for vehicle windows, the sealing member addresses the neglect of driving performance improvement, achieving effective static elimination and enhanced steering stability.
Patent Information
- Application Number
- JP2021108545
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-30
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2041-06-30
AI Technical Summary
Existing sealing members for vehicle windows primarily focus on preventing rainwater and dust intrusion, neglecting their potential contribution to improving driving performance such as steering stability.
Incorporating a flocked layer with conductive fibers into the sealing member that comes into sliding contact with the window glass, enhancing static elimination and thereby improving driving stability.
The sealing member effectively reduces electrostatic charge on the window glass, leading to improved steering stability without increasing costs by integrating a separate static eliminator.
Smart Images

Figure 0007657666000004 
Figure 0007657666000005 
Figure 0007657666000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a seal member for use with a window pane in a vehicle. [Background technology]
[0002] When an openable window is provided in a vehicle such as an automobile, a sealing member is provided to prevent rainwater and dust from entering through a gap between the window glass and the vehicle body, and the window glass slides against the sealing member as the window glass moves. One example of such a sealing member is a weather strip that seals the gap between the door glass and the door panel in a vehicle door to prevent water and dust from entering the inside of the door body. Patent Document 1 shows an example of a specific configuration of a weather strip. Patent Document 2 discloses electrostatic flocking of fibers via an adhesive on the surface of the weather strip that slides against the window glass.
[0003] By the way, it is known that in vehicles such as automobiles, the body of the vehicle generally becomes positively charged as the vehicle runs on the road surface, and that the electrostatic charge of the body affects driving performance such as steering stability. Since the air in the environment is usually positively charged, the positively charged air flow flowing around the vehicle body during driving repels the positively charged vehicle body electrically, which makes it easier for the air flow to separate from the outer surface of the vehicle body, and it is thought that this affects the steering stability of the vehicle. For example, Patent Document 3 discloses that a self-discharging static eliminator is provided at a location where the air flow may separate from the vehicle body during driving, which neutralizes and eliminates the positive charge on the vehicle body side by self-discharging, thereby preventing the separation of the air flow and improving the steering stability of the vehicle. One example of a self-discharging static eliminator is a conductive aluminum adhesive tape whose outer edge is processed to have sharp or pointed corners. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5618950 [Patent Document 2] Patent No. 4171547 [Patent Document 3] Patent No. 6168157 Summary of the Invention [Problem to be solved by the invention]
[0005] In the past, attention was focused on the sealing members used for window glass in vehicles such as automobiles only for their function of preventing the intrusion of rainwater, etc. However, in recent years, with the improvement in the performance of vehicles, there has been an increasing demand for sealing members to contribute to the improvement of driving performance such as steering stability.
[0006] An object of the present invention is to provide a sealing member for use with a window glass of a vehicle, which also contributes to improving the driving performance, such as the driving stability, of the vehicle. [Means for solving the problem]
[0007] As described in Patent Document 3, a technology is known for improving the driving performance such as the driving stability of a vehicle by providing a self-discharging static eliminator to the vehicle body, but this technology reduces the amount of charge on the metal part of the vehicle body using a static eliminator made of aluminum adhesive tape or the like, so the cost increases by providing the static eliminator. The present inventors therefore considered providing a static eliminator function to a seal member used for window glass, and found that the driving stability of a vehicle can be improved by providing a flocked layer on the part of the seal member that comes into sliding contact with the window glass and including conductive fibers in the fibers planted in the flocked layer, thus completing the present invention. Thus, the seal member of the present invention is characterized in that, in a seal member used for a vehicle window glass and in sliding contact with the window glass, a flocked layer with fibers planted therein is formed on at least a part of the surface, and the fibers planted in the flocked layer contain conductive fibers.
[0008] In the sealing member of the present invention, the blending ratio of the conductive fibers in the fibers planted in the flocking layer is 1% by mass or more and 5% by mass or less. the law of nature , 1.5% by mass or more and 2.5% by mass or less I like I wish. The conductive fibers have a core-sheath structure in which a polymer material containing conductive particles is disposed in the core portion, and the sheath portion surrounding the core portion is composed only of the polymer material. In addition, based on JIS (Japanese Industrial Standards) L1094, the surface of the flocked layer is charged by corona discharge with an applied voltage of -10 kV with a clearance of 20 mm, and the initial charged voltage is the charged voltage on the surface of the flocked layer, and the half-life is the time until the charged voltage on the surface of the flocked layer becomes half of the initial charged voltage after the corona discharge is stopped. The charge decay, which is the value obtained by dividing half of the initial charged voltage by the half-life, is preferably 0.20 kV / sec or more. In measuring the charge decay, for example, the thickness of the test piece is 3.3 mm.
[0009] One example of the sealing member of the present invention is a weatherstrip having a base attached to a panel of a vehicle body, and a lip portion made of a material different from the base, connected to the base, and provided with a flocked layer that comes into sliding contact with the window glass. When the sealing member is configured as a weatherstrip, it is preferable that the flocked layer in the lip portion is formed from the portion that comes into sliding contact with the window glass to the portion that does not come into sliding contact with the window glass. Effect of the Invention
[0010] According to the present invention, it is possible to obtain a sealing member that is used for a window glass of a vehicle and that also contributes to improving the driving performance, such as the handling stability, of the vehicle. [Brief description of the drawings]
[0011] [Figure 1] 1(a) and 1(b) are cross-sectional views showing a weather strip according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing the arrangement of weather strips and potential measurement points on a rear door of a vehicle. [Diagram 3] FIG. 2 is a cross-sectional view showing a test piece used in measuring charge decay. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Next, an embodiment of the present invention will be described with reference to the drawings. The sealing member according to the present invention is used for a window glass of a vehicle to prevent the intrusion of rainwater and dust, and is in sliding contact with the window glass as the window glass moves, for example, when the window glass is opened or closed. A flocked layer with fibers flocked therein is formed on the surface of the sealing member in a portion that is in sliding contact with the window glass in order to enhance sealing properties. In the flocked layer, the fibers are flocked, for example, via an adhesive, but the flocked layer may be formed by attaching a tape with fibers flocked thereto to the sealing member. The sealing member according to the present invention is characterized in that the fibers flocked in the flocked layer contain conductive fibers. According to the findings obtained by the inventors as described below, the fibers constituting the flocked layer contain conductive fibers, thereby suppressing the electrostatic charge of the window glass during the running of the vehicle, and as a result, the steering stability of the vehicle is improved. As an example, the sealing member according to the present invention is a weather strip that is attached to a door panel of a vehicle door to prevent the intrusion of rainwater and the like into the door body when the door glass is opened or closed. Hereinafter, the sealing member according to the present invention will be described assuming that the sealing member is a weather strip.
[0013] FIG. 1(a) is a cross-sectional view showing a weatherstrip 10 according to an embodiment of the present invention, and FIG. 1(b) is a cross-sectional view showing the weatherstrip 10 in use. FIG. 2 shows an example of a vehicle door 30 to which the weatherstrip 10 is attached. The door 30 shown in FIG. 2 is the rear left door of a sedan-type automobile, and FIG. 2 depicts the door 30 as seen from the passenger compartment side. FIG. 2 also depicts a door handle 32 provided on the passenger compartment side of the door 30. The weatherstrip 10 is an elongated member extending along the surface of the door glass 40, and FIG. 1 depicts a cross section of the weatherstrip 10 in a plane perpendicular to the longitudinal direction. In the weatherstrip 10, a base 11 attached to a panel portion of the vehicle body, specifically, a door panel 35, and a lip portion 12 that is a portion that slides against the door glass 40 are integrally formed. The base 11 is made of, for example, hard polypropylene (PP), and the lip portion 12 is made of, for example, soft olefin-based thermoplastic elastomer (TPO). The lip portion 12 is formed so that one end thereof is connected to the base portion 11. The lip portion 12, which is made of a material softer than the base portion 11, is deformed so as to bend when the door glass 40 slides against it, as shown in Fig. 1(b), so that the weather strip 10 slides against the door glass 40 over a wider area.
[0014] A flocked layer 20, in which fibers are flocked via an adhesive, is provided on the surface of the lip portion 12 so as to be in actual sliding contact with the door glass 40. As can be seen from FIG. 1(b), the flocked layer 20 is formed on the surface of the lip portion 12 from the portion with which the door glass 40 slides to the portion with which the door glass 40 does not slide. The fibers flocked in the flocked layer 20 contain conductive fibers. The blending ratio of the conductive fibers in the fibers flocked in the flocked layer 20 is preferably 1% by mass or more and 5% by mass or less, and more preferably 1.5% by mass or more and 2.5% by mass or less. The conductive fibers are preferably fibers having a resistivity of the fiber alone, i.e., a conductive fiber resistance of 4×10 Ω·cm or more and 4×10 2A conductive fiber having a resistance of Ω·cm or less can be preferably used. If the conductive fiber resistance is smaller than this range, the static elimination effect will be higher, but the cost will be significantly higher. On the other hand, if the conductive fiber resistance is too high, the static elimination effect will be reduced. In the flocked layer 20, the conductive fibers are mixed into and flocked with pile made of polyethylene terephthalate (PET) fiber or nylon fiber.
[0015] The conductive fiber may be manufactured, for example, by dissolving a polymer material that is the raw material of the fiber, adding conductive particles, such as carbon or titanium oxide, thereto, and then spinning the molten polymer. However, from the viewpoint of strength, for example, it is preferable to use a conductive fiber having a core-sheath structure or a conductive fiber in which a conductive portion is formed on the fiber surface at a specific circumferential position so as to extend in the longitudinal direction of the fiber. In the conductive fiber having a core-sheath structure, a polymer material containing conductive particles is disposed in the core portion, and the sheath portion surrounding the core portion is composed only of a polymer material. As an example, a conductive fiber having a core-sheath structure in which a layer containing a lot of carbon is used as the core portion, the sheath portion is composed of acrylic, and the diameter of the core portion is 10 μm can be used. An example of a conductive fiber having a core-sheath structure that can be used in this embodiment is Corebrid B (trade name) manufactured by Mitsubishi Chemical Corporation. In addition, an example of a conductive fiber in which a conductive portion is formed on the fiber surface at a specific circumferential position so as to extend in the longitudinal direction of the fiber is Kuraray Co., Ltd.'s Kuracarbo (registered trademark) KC-585S.
[0016] Next, the position of the weather strip 10 of the present embodiment when provided on the door 30 of the vehicle will be described. Assuming that the door glass 40 is stored in the door body 31 when the window is opened, the weather strip 10 is provided at the position indicated by the dotted line A in FIG. 2 along the upper part of the door body 31 and the opening through which the door glass 40 enters and exits for opening and closing the window. The area 40a indicated by the dashed line in the figure indicates a part of the door glass 40 that exists inside the door body 31 even when the window is completely closed. Even when the window is completely closed, the weather strip 10 slides against a part of the door glass 40. Furthermore, the weather strip 10 may be provided at a position indicated by the dotted line B in FIG. 2 called a run channel. In general, in a vehicle, the weather strip for the door glass 40 is provided in pairs on the inside and outside of the vehicle with the door glass 40 sandwiched therebetween, and they are called the door glass inner weather strip and the door glass outer weather strip, respectively. The weatherstrip 10 of this embodiment may be applied to both the inner weatherstrip and the outer weatherstrip, or the weatherstrip 10 of this embodiment may be applied to either the door glass inner weatherstrip or the door glass outer weatherstrip, and a weatherstrip not containing conductive fibers may be applied to the other. By applying the weatherstrip 10 of this embodiment to at least one of the door glass weatherstrips sandwiching the door glass 40, a static elimination effect due to the conductive fibers is exerted, suppressing the charging of the door glass 40, thereby improving the handling stability of the vehicle.
[0017] Next, a method for manufacturing the weather strip 10 of this embodiment will be described. First, a long base material is obtained by extrusion molding of hard PP and soft TPO. In the base material, the base 11 and the lip portion 12 are formed collectively. Next, the surface of the lip portion 12 formed of soft TPO is subjected to a primer treatment in an area where the flocked layer 20 will be formed, and an adhesive is applied to the area where the primer treatment has been performed. Then, pile made of PET fiber mixed with conductive fiber is electrostatically flocked to form the flocked layer 20. As a specific procedure for electrostatic flocking, the one described in Patent Document 2 can be used. Finally, the base material on which the flocked layer 20 has been formed is cut to a desired length to complete the weather strip 10.
[0018] According to the present embodiment described above, simply mixing conductive fibers into the flocked portion of the seal member promotes static elimination of the vehicle window glass, improving the vehicle's driving stability. Compared to the conventional method using an aluminum adhesive tape static eliminator, this method does not require a separate static eliminator, so it is possible to achieve a similar improvement in driving stability at a low cost. In addition, by using conductive fibers of the same color as the black flocked layer that is widely used in vehicle seal members, it is possible to eliminate static electricity from the window glass without compromising the design of the seal member, even though it is used in a place where the user can see it. EXAMPLES
[0019] Next, the present invention will be described in more detail with reference to examples and comparative examples.
[0020] [Example 1: Evaluation of steering stability] A four-door type four-wheel passenger car was prepared, and the inner weather strips at the positions A shown in FIG. 2 were replaced in the four doors of the vehicle, and test runs were conducted for the case where the inner weather strip had conductive fibers planted in the flocked layer 20 (hereinafter also referred to as the "invented product") and the case where the inner weather strip had no conductive fibers planted in the flocked layer 20 (hereinafter also referred to as the "current product"), and a subjective evaluation of the driving stability was performed by a test driver. The inner weather strip used was the same as that shown in FIG. 1, and was formed integrally with a base 11 made of hard PP and a lip 12 made of soft TPO and connected to the base 11, and the flocked layer 20 was formed on the surface of the lip 12 at a position where it would slide against the door glass 40. The flocked layer 20 was made of PET fiber pile with a thickness of 1.7T (decitex) and a length of 0.8 mm. When conductive fibers were mixed and planted in the planted layer 20, Corebrid B (product name) manufactured by Mitsubishi Chemical Corporation with a diameter of 20 μm was used as the conductive fibers, which were cut to a length of 0.8 mm so that the proportion of conductive fibers in the planted fibers was 2 mass%. The outer weather strips used for each door did not contain conductive fibers.
[0021] The test drive was conducted by three test drivers driving the test vehicle on the same flat test course. At that time, the test drivers were not informed of whether the vehicle had conductive fibers or not. As a result of the test drive, all three test drivers answered that the driving stability was higher when the weather strip with conductive fibers was used.
[0022] [Example 2: Measurement of potential on window glass] When the test run of Example 1 was carried out, the electrostatic potential of the door glass of the rear left door was measured from the passenger compartment side using a static electricity meter (Keyence Corporation, Model SK-H050). The electrostatic potential on the window glass was measured at five points, points P, Q, R, S, and T in Figure 2. The results are shown in Table 1. Table 1 also shows the average potential measured at the five measurement points.
[0023] [Table 1]
[0024] In Table 1, Run 1 to Run 3 respectively indicate test runs by three test drivers. The weather during the test runs was fine, and for Run 1, the running time was about 60 minutes for each run, the temperature during the test run of the current product was 25°C and the humidity was 57%, and the temperature during the test run of the invented product was 28°C and the humidity was 64%. For Run 2, the running time was about 40 minutes for each run, the temperature during the test run of the current product was 23°C and the humidity was 56%, and the temperature during the test run of the invented product was 27°C and the humidity was 60%. For Run 3, the running time was about 60 minutes for each run, the temperature during the test run of the current product was 18°C and the humidity was 54%, and the temperature during the test run of the invented product was 22°C and the humidity was 52%. In the results shown in Table 1, when the current inner weather strip, which does not contain conductive fibers in the flock layer, was used, the electrostatic potential increased at the time of arrival compared to the time of departure, whereas when the inner weather strip of the invention, which contains conductive fibers in the flock layer, was used, the electrostatic potential at the time of arrival was generally decreased compared to the time of departure. In other words, it was found that the inner weather strip of the invention, which contains conductive fibers in the flock layer, has an electrostatic removal effect that reduces the amount of electrostatic charge on the door glass.
[0025] [Example 3: Study on the blending ratio of conductive fibers] In order to create a test piece simulating a weather strip and verify the static elimination effect, a static electricity decay measuring instrument (static honest meter) MODEL H0110 manufactured by Shishido Electrostatic Corporation was used in accordance with JIS (Japanese Industrial Standards) L1094 to measure the initial charging voltage and half-life under an environment of 20±2°C and relative humidity of 40±2%, and to obtain the charge decay degree. In the measurement, the test piece was placed on a turntable, and the turntable was rotated so that the test piece went back and forth between the application part and the receiving part of the measuring instrument, and the surface of the test piece was charged by corona discharge with an applied voltage of -10 kV at the application part, and the charging voltage of the test piece was measured at the receiving part. The rotation speed of the turntable was 1550 revolutions per minute, the clearance of the application part was 20 mm, and the clearance of the receiving part was 15 mm. The size of the test piece was 45 mm x 45 mm, and the plate thickness of the test piece was 3.3 mm.
[0026] Six types of test pieces 1 to 6 were prepared. FIG. 3 shows the cross-sectional structure of the test pieces. A primer and an adhesive were applied to one surface of a base material 51 made of soft TPO to form an adhesive layer 52, and a flocked pile 53 made of PET fiber was flocked to the adhesive layer 52 to prepare the test pieces. However, in the test piece 1, the flocked pile 53 was made of only PET fiber, in the test piece 2, 1 mass % of conductive fiber was blended into the flocked pile 53, in the test piece 3, 2 mass % of conductive fiber was blended into the flocked pile 53, and in the test piece 4, 4 mass % of conductive fiber was blended into the flocked pile 53. In addition, the test piece 1 was made of only the base material 51, and the test piece 2 was made of the base material 51 and an adhesive layer 52. Corebrid B (trade name) manufactured by Mitsubishi Chemical Corporation was used as the conductive fiber. In the test piece, the side of the flocked pile 53 was set as the front side and the side of the base material 51 was set as the back side, and the charge decay was measured on both sides.
[0027] When a test piece is placed on a turntable and a corona discharge is induced in the application section while the turntable is rotating, charge accumulates on the surface of the test piece, and the charging voltage due to the accumulated charge is measured in the receiving section. As charge accumulates over time, the charging voltage gradually increases and eventually settles down to a constant value. The charging voltage at this point is called the initial charging voltage V0. The initial charging voltage can be considered to be the charging voltage of a surface when it is charged by a corona discharge with an applied voltage of -10 kV with a clearance of 20 mm. When the charging voltage settles down to a constant value, the corona discharge in the application section is stopped. The charging voltage of the test piece then decreases. The time from the cessation of the corona discharge until the charging voltage of the test piece becomes half of the initial charging voltage, i.e., V0 / 2, is called the half-life t 1 / 2 And the half-life is t 1 / 2 The voltage drop (i.e., V0 / 2) during the half-life t 1 / 2 The charge decay rate c is calculated by dividing by . This can be expressed as follows: c = V0 / (2 × t 1 / 2 ) Here, five measurements were taken for each test piece, and the average values were used to determine the charge decay, initial charging voltage, and half-life of the test piece. The results are shown in Table 2.
[0028] [Table 2]
[0029] It was found that the charge was hardly attenuated on the back side of the test specimen, i.e., the side of the substrate 51, and that the charge deactivation effect could not be expected on this side. On the other hand, when the measurement results of the charge deactivation on the front side of the test specimen were compared, it was found that the flocked pile 53 had a large effect on the charge deactivation, and the charge deactivation increased when conductive fibers were blended into the flocked pile 53. In other words, it was found that blending conductive fibers into the flocked pile is effective for improving the charge deactivation effect. The flocked pile 53 in the test specimen corresponds to the flocked layer 20 in the weather strip 10 shown in FIG. 1, and the results shown in Table 2 show that the blending ratio of conductive fibers in the flocked pile is preferably 1% by mass or more and 5% by mass or less. However, when the blending ratio of conductive fibers exceeds 2% by mass, the effect of increasing the charge deactivation tends to plateau, so the blending ratio of conductive fibers is more preferably 1.5% by mass or more and 2.5% by mass or less. In addition, when the relationship between the blending ratio of conductive fibers and the charge deactivation is taken into consideration, it is found that the charge deactivation is preferably 0.20 kV / sec or more.
[0030] [Example 4: Comparative experiment with static elimination using aluminum tape] A vehicle similar to that used in Example 1 was used. A comparison was made between a case where conductive fibers were mixed into the hair-planted layer of the weather strip based on the present invention as a means for eliminating static electricity, and a case where aluminum tape, which is a self-discharge type static eliminator, was used. In the case where conductive fibers were mixed into the hair-planted layer, a vehicle was constructed in the same manner as in the "invention product" of Example 1. In the case where aluminum tape was used (hereinafter also referred to as "use of aluminum tape"), a vehicle was constructed by attaching aluminum tape to each of the four door glasses 40 of the vehicle in the case of the "current product" of Example 1. The aluminum tape was 10 mm x 40 mm in size, and was attached via a conductive adhesive to both ends of the surface of the door glass 40 facing the passenger compartment, which is hidden inside the door body 31 even when the window is completely closed. The position where the aluminum tape was attached is shown as the area surrounded by the dashed lines C and D in FIG. 2. Test runs were performed for these two cases in the same manner as in Example 1. However, the test runs were performed by two test drivers. Then, the electrostatic potential of the door glass of the rear left door was measured immediately before the start and immediately after the end of the test drive, in the same manner as in Example 2. The results are shown in Table 3.
[0031] [Table 3]
[0032] In Table 3, Run 4 and Run 5 each show a test run by two test drivers. The weather during the test run was fine, and for Run 4, the running time was about 60 minutes. The temperature during the test run using aluminum tape was 27°C and the humidity was 55%, and the temperature during the test run of the invention was 28°C and the humidity was 53%. For Run 5, the running time was about 60 minutes, the temperature during the test run using aluminum tape was 29°C and the humidity was 56%, and the temperature during the test run of the invention was 28°C and the humidity was 58%. In the results shown in Table 3, even when using aluminum tape, which is a self-discharging static eliminator, the charge potential at the time of arrival was generally reduced compared to the time of departure, similar to the case of using the inner weather strip of the invention containing conductive fibers in the flock layer. In other words, it was found that the amount of charge on the door glass can be reduced similarly to the case of using the inner weather strip of the invention containing conductive fibers in the flock layer by using aluminum tape, and from this, it can be inferred that the steering stability is similarly improved by applying aluminum tape to the door glass. However, attaching aluminum tape to the door glass 40 is disadvantageous in terms of production costs and work time compared to mixing conductive fibers into the flocked layer already provided in the weather strip and flocking them, in terms of the costs of the aluminum tape and conductive adhesive, the time required for the attachment work, etc. In other words, by using the sealing member based on the present invention, it is possible to realize a configuration that reduces the amount of static electricity on the window glass at lower cost and in a shorter work time than when a self-discharge static eliminator using aluminum tape or the like is provided. [Explanation of symbols]
[0033] 10 Weather strip 11 Base 12 Lip 20 Flocking layer 35 Door Panel 40 Door Glass
Claims
1. A seal member used for a vehicle window glass in sliding contact with the window glass, A flocked layer in which fibers are flocked is formed on at least a part of the surface, The fibers planted in the flocked layer contain conductive fibers, The blending ratio of the conductive fibers in the fibers planted in the flocked layer is 1 mass% or more and 5 mass% or less, A sealing member, characterized in that the conductive fiber has a core-sheath structure in which a polymer material containing conductive particles is disposed in a core portion, and the sheath portion surrounding the core portion is composed only of a polymer material.
2. 2. The sealing member according to claim 1, wherein the charge decay rate is 0.20 kV / sec or more, the charge voltage of the surface of the flocked layer being an initial charge voltage when the surface of the flocked layer is charged by corona discharge with an applied voltage of -10 kV with a clearance of 20 mm based on JIS L1094, the half-life being the time until the charge voltage of the surface of the flocked layer becomes half of the initial charge voltage after the corona discharge is stopped. The charge decay rate is calculated by dividing half of the initial charge voltage by the half-life.
3. the sealing member is a weather strip having a base portion attached to a panel portion of a body of the vehicle, and a lip portion made of a material different from the base portion, connected to the base portion, and provided with the flocked layer that is in sliding contact with the window glass; 3. The seal member according to claim 1, wherein the flocked layer is formed in the lip portion from a portion with which the window glass slides to a portion with which the window glass does not slide.
Citation Information
Patent Citations
Metod of manufacturing tetrafluoroboric acid diazonium in dilute aqueous solution
JP1981018950A
Nozzle for spraying concrete or refractory capable of controlling spouting liquid pressure to specified value
JP1986068157A
Molded object made of synthetic resin
JP2001301075A
Belt molding
JP2002219944A
Resin composition, method for producing the same and use of the same
JP2009127038A